Physiological and performance changes in response to pre-season training in high level handball players - Milanez, V. F.; Ramos, S. P.; Lepretre, P.-M.; Leme, L. C.; Nakamura, F. Y. (Science & Sports, 2014)
Introduction: The aim of this study was to evaluate changes of physiological markers and performance, in professional handball players during the pre-season period. Summary of facts: Fifteen male players (mean and SD: age 24.0 ± 4.0 years, body mass 89.7 ± 10.1 kg and height 185.2 ± 6.3 cm) participated in this study. The evaluations of physical performance, cardiac autonomic modulation and the collection of blood samples for inflammatory markers were conducted at beginning of pre-season (M1) and 7 weeks after (M2). There were significant increases of performance in the Yo-YoIR2, vertical jumps and significant reduction in TGF-ß. Small to large effect size (ES) for changes were detected for SDNN, RMSSD, LF + HF and SD1 indexes. Conclusions: The pre-season period has promoted positive changes in global indices of cardiac autonomic modulation, TGF-ß together with an increase of physical performance.